A Coded MIMO-OFDM System’s Performance Comparison of the Spatial Channel Model and the Onering Channel Model Based on Interpolation Techniques - Nguyen, Thu Nga; Nguyen, Van Duc; Ta, Phuong Nam; Tran, Quoc Toan (Old Journal, 2019)
In this paper, we consider to estimate the channel coefficient in the wideband and frequency selective multi-input multi-output orthogonal frequency division multiplexing (MIMO-OFDM) system. The simulation is based on two channel models, one has been proposed by the 3rd Generation Partnership Project (3GPP) standard - the Spatial Channel Model (SCM) and the other is the Onering channel model, under the LTE Advanced standard for 4G in the suburban macro-cell environment. The obtained results show the symbol error rate (SER) value when using different interpolations (Linear, Sinc or Wiener) with the same input parameters. The Space Frequency Block Coding (SFBC) and minimum mean-squared error (MMSE) equalizer are also used for the simulation of the MIMO 2x2 systems. The SER results in the SCM channel model are lower than that obtained by the Onering channel model when employing the different interpolation methods.